How to make school make sense a parents' guide to helping the child with Asperger syndrome - Lawrence, Clare (Jessica Kingsley Publishers, 2008)
Every child's education relies on a partnership between parents, professionals and, of course, the child. This book gives parents of children with Asperger syndrome (AS) practical advice on how to make the most of this important partnership and work with schools to ensure their child's needs are being met.
Keywords: Autistic children : Education; Education : Parent participation; Asperger's syndrome in children